Improvement of smallholder farming systems in Africa - Wortmann, Charles S.; Amede, Tilahun; Bekunda, Mateete A.; Ndung’u-Magiroi, K.; Masikati, Patricia; Snapp, Sieglinde S.; Stewart, Zachary P.; Westgate, M.; Zida, Z.; Kome, C.E. (Wiley, 2020)
This forum paper provides a synthesis and discussion of 14 categories of lessons learned from experiences for achieving farm‐level impact with smallholder farmers in Africa. These lessons were reported in a symposium hosted by the Agronomy in Africa community of the American Society of Agronomy. The lessons, listed in order of frequency of reporting, were the need to: have adequate infrastructure and services; enable spontaneous adoption; have multi‐disciplinary and institutional collaboration; build on previous adoption of good agronomic practices (GAP); have farmer participation in research; encourage and learn from smallholder adaptations; make GAP promotion demand‐driven; allow GAP choices; address challenges and trade‐offs to GAP adoption; enable GAP‐by‐GAP adoption; reconcile conflicting messages; offer adequate profit potential with acceptable risk; reduce labor needs, especially for women; and build capacity for farming system improvement along the chain from farmer to research. The lessons are discussed and conclusions are reported.